Carbohydrate supplementation and resistance training - Haff, G. G.; Lehmkuhl, M. J.; McCoy, L. B.; Stone, M. H. (The Journal of Strength and Conditioning Research, 2003)
There is a growing body of evidence suggesting that the performance of resistance-training exercises can elicit a significant glycogenolytic effect that potentially could result in performance decrements. These decrements may result in less than optimal physiological adaptations to training. Currently some scientific evidence suggests that carbohydrate supplementation prior to and during high-volume resistance training results in the maintenance of muscle glycogen concentration, which potentially could result in the maintenance or increase of performance during a training bout. Some researchers suggest that ingesting carbohydrate supplements prior to and during resistance training may improve resistance-training performance. Additionally, the ingestion of carbohydrates following resistance exercise enhances the resynthesis of muscle glycogen, which may result in a faster time of recovery from resistance training, thus possibly allowing for a greater training volume. On the basis of the current scientific literature, it may be advisable for athletes who are performing high-volume resistance training to ingest carbohydrate supplements before, during, and immediately after resistance training.